2019
DOI: 10.21608/jsrs.2019.57630
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence, structural, morphology and dielectric properties of BaTi0.9Sn0.1O3 doped with Nd3+ and Nd3+/ Yb3+ ions

Abstract: Nano-structure BaTi 0.9 Sn 0.1 O 3 (BTSO) doped with Nd 3+ (BTSO: 5N) and co-doped with Nd 3+ /Yb 3+ ions (BTSO: 5NY), were prepared using the modified sol-gel method in powder form and annealed at 1050 o C in air for 4h. Their structural, morphological, photoluminescence and dielectric properties studies were investigated. The crystallite sizes from XRD and TEM found to be decreased upon doping with Nd 3+ and Nd 3+ /Yb 3+ ions, respectively. FTIR results showed enhancement of crystallinity and absence of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(11 reference statements)
2
0
0
Order By: Relevance
“…Where Yb 3+ ions with larger ionic radius than Ti 4+ led the deformation of BTSO: 0.5Er perovskite structure and a reduction in its tetragonality, thus inducing a drop in the Curie temperature, and more drop induced with increasing Yb 3+ ions doping concentration. From our previously report about BTSO its permittivity is equal to 2520 [19], comparing this result; the permittivity increased for BTSO: 0.5Er and BTSO: 0.5Er1Yb, it was found to be equal to 3972 and 6071, respectively at both the T C temperature and the constant frequency measured at 10 2 Hz. The increase in the permittivity can be due to the modifications in the crystallite size as seen in Table 1, resulting from Er 3+ and Er 3+ /Yb 3+ ions doping in the BTSO structure.…”
Section: Fesem Characterizationsupporting
confidence: 57%
See 1 more Smart Citation
“…Where Yb 3+ ions with larger ionic radius than Ti 4+ led the deformation of BTSO: 0.5Er perovskite structure and a reduction in its tetragonality, thus inducing a drop in the Curie temperature, and more drop induced with increasing Yb 3+ ions doping concentration. From our previously report about BTSO its permittivity is equal to 2520 [19], comparing this result; the permittivity increased for BTSO: 0.5Er and BTSO: 0.5Er1Yb, it was found to be equal to 3972 and 6071, respectively at both the T C temperature and the constant frequency measured at 10 2 Hz. The increase in the permittivity can be due to the modifications in the crystallite size as seen in Table 1, resulting from Er 3+ and Er 3+ /Yb 3+ ions doping in the BTSO structure.…”
Section: Fesem Characterizationsupporting
confidence: 57%
“…Figure 1 shows the XRD patterns of BTSO: 0.5Er (A), BTSO: 0.5Er0.75Yb (B) and BTSO: 0.5Er1Yb (C) powders calcinated at 1050˚C for 4h in air. XRD [19]. In the present work (Figure 1) represent BTSO doped samples (A, B, and C), from Figure 1, it is clearly observed that SnO 2 traces still present with various intensities.…”
Section: X-ray Diffractionsupporting
confidence: 56%